PENGARUH BELANJA PENDIDIKAN, BELANJA KESEHATAN DAN BELANJA INFRASTRUKTUR TERHADAP INDEKS PEMBANGUNAN MANUSIA DI PROVINSI SULAWESI SELATAN TAHUN 2013 – 2022 - Hartanto, Tomi; Idrus, Jemmy; Virniasari, Virniasari (Transpublika Publisher, 2023)
Quality development does not merely reflect economic growth, but also refers to improving people's welfare as the main goal of development. A key role in achieving this goal is given to human development, which plays a vital role in improving people's welfare. Assessment of the level of community welfare generally uses certain indicators, and one of them is the Human Development Index (HDI). Government intervention in promoting human development is reflected in the allocation of functional expenditure on three main functions, namely health, education and infrastructure. The results show that partially, health spending has a negative but insignificant influence on welfare improvement. Meanwhile, infrastructure spending shows a positive but insignificant effect. On the other hand, education spending has a significant positive effect on improving community welfare. Overall, the three types of expenditure simultaneously had a significant effect on improving the Human Development Index in South Sulawesi Province. The implications of these findings can assist the government and stakeholders in designing more effective policies to accelerate human development and improve community welfare at the regional level.